Research and development in drug innovation: reflections from the 2013 bioeconomy conference in China, lessons learned and future perspectives - Changxiao Liu; Panayiotis P. Constantinides; Yazhuo Li (Elsevier, 2014)
The enormous progress biotechnology, bioinformatics and nanotechnology made in recent years provides opportunities and scientific framework for development of biomedicine and constitutes a paradigm shift in pharmaceutical R&D and drug innovation. By analyzing the data and related information at R&D level over the past decades, developmental tendency and R&D patterns were summarized. We found that a growing number of biologics in the pipeline of pharma companies with successful products already in the market though, small molecular entities have primarily dominated drug innovation. Additionally, small/medium size companies will continue to play a key role in the development of small molecule drugs and biologics in a multi-channel integrated process. More importantly, modern and effective R&D strategies in biomedicine development to predict and evaluate efficacy and/or safety of 21st century therapeutics are urgently needed. To face new challenges, developmental strategies were proposed, in terms of molecular targeted medicine, generic drugs, new drug delivery system and protein-based drugs. Under the current circumstances, interdisciplinary cooperation mode and policy related to drug innovation in China were deeply discussed as well.